The Effects of Aerobic Training on Depression and Resilience among Healthcare Workers - Hassan Shafaei (Journal of Modern Psychology)
Objective: Identifying factors that can positively influence the mental health and resilience of healthcare workers is crucial. As such, this research aims to explore the impact of aerobic exercise on depression and resilience among healthcare workers. Methods: This study was conducted as an experiment, focusing on healthcare workers employed in hospitals in Tehran. A sample of 64 health care workers was selected using a convenience sampling method. These individuals were then randomly divided into two control groups (32 people each) and one experimental group (32 people). Data was collected using standard questionnaires. T tests and ANCOVA were used to analyze data. Results: The results showed that there is no significant difference in both depression and resilience in the pretest (both P>0.05). However, it was observed that experimental group had significantly lower depression and higher resilience compared to control group in the posttest (both P=0.001). Finally, the results of ANCOVA showed significant differences between experimental and control groups in both depression and resilience (both P=0.001).Conclusion: These results suggest that physical activity and sport can be considered as an important factor in coping with severe job-related conditions in healthcare workers. Therefore, by increasing physical activity and sport, better conditions can be created for healthcare workers to ensure their mental health.